LITERASI MEDIA MAHASISWA PERGURUAN TINGGI NEGERI KOTA KENDARI TERHADAP ISU SARA PADA MEDIA SOSIAL - sri Hadijah Arnus (Institut Agama Islam Negeri Kendari, 2019)
This study aims to analyze literacy media among state university students in Kendari regarding the issue of SARA in social media and to provide solutions to enhance the student’s media literacy skills. This study is design in descriptive qualitative approach. Required data for this study were collected through snowball sampling. Data analysis was carried out using Individual Competence Framework. This study reveals that the level of media literacy skills of the students was classified as basic. In other words, the students had basic skills to utilize the media and had limited media usage. The users understood the basic functions, reveal the basic codes and use them for final objectives. The students’ ability to critically analyze the received information was limited. As a result, the ability to communicate through the media was also limited. The solutions to improving media literacy skills of state university students in Kendari can be through incorporating knowledge regarding media literacy in the curriculum of study programs, conducting research related to media literacy among lecturers and students, holding trainings and workshops, providing media literacy knowledge through leader opinions such as religious leaders and community leaders, and developing religious studies on campus.